Peningkatan Prestasi Belajar Pendidikan Agama Islam (PAI) melalui Gerakan Literasi pada Siswa Madrasah Tsanawiyah di Aceh Barat Daya - Wahab, Imrullah (Tadabbur: Jurnal Peradaban Islam, 2022)
The implementation of the literacy program at Madrasah Tsanawiyah in Southwest Aceh Regency which simultaneously started in 2015 has shown positive results in increasing student achievement, but the program has not been able to raise the achievement of madrasas at the provincial level, especially in PAI Subjects. In implementing the literacy program, each madrasa applies a pattern designed according to the conditions of the madrasa. The literacy pattern applied to some madrasas is less effective, so it has less effect on increasing student achievement. The purpose of this research is to describe the improvement of PAI learning achievement through literacy movement at Madrasah Tsanawiyah in Southwest Aceh Regency and to describe the pattern of application of literacy movement at Madrasah Tsanawiyah in Southwest Aceh Regency in an effort to improve PAI learning achievement. This research is a qualitative research, data collection in this research is done through document study, observation and interviews. The results showed that: First, the implementation of the literacy movement program at MTsN 1 and MTsN 4 Aceh Barat Daya directly or indirectly had a positive influence on improving student achievement in PAI subjects (Akidah-Akhlak, Al-qur'an-Hadith, Jurisprudence, and SKI) both academically and non-academicly. Second, the pattern of implementing the literacy program at the two madrasas (MTsN 1 and MTsN 4 Aceh Barat Daya) is very different, where MTsN 1 applies a regular and varied pattern for each level, so as to achieve optimal student achievement in PAI subjects. . While MTsN 4 applies a very simple and not varied pattern, so that it becomes one of the causes of the less than optimal achievement of student achievement in PAI subjects.